2017
DOI: 10.1071/fp16154
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in soil water use and root distribution and their implications for drought tolerance in chickpea

Abstract: Abstract. Chickpeas are often grown under receding soil moisture and suffer~50% yield losses due to drought stress. The timing of soil water use is considered critical for the efficient use of water under drought and to reduce yield losses. Therefore the root growth and the soil water uptake of 12 chickpea genotypes known for contrasts in drought and rooting response were monitored throughout the growth period both under drought and optimal irrigation. Root distribution reduced in the surface and increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 109 publications
2
42
1
Order By: Relevance
“…The water holding capacity of this field in lower limit: upper limit was 0.26:0.40 cm 3  cm −3 for the 0–15 cm soil layer, and 0.30:0.47 cm 3  cm −3 for the 105–120 cm soil layer. The available soil water up to 120 cm depth observed in this study was 216 mm in 2009–10 and 207 mm in 2010–11 (Purushothaman et al, 2016a). The bulk density was 1.35 g cm −3 for the 0–15 cm soil layer and 1.42 g cm −3 for the 105–120 cm soil layer (El-Swaify et al, 1985).…”
Section: Methodsmentioning
confidence: 53%
See 4 more Smart Citations
“…The water holding capacity of this field in lower limit: upper limit was 0.26:0.40 cm 3  cm −3 for the 0–15 cm soil layer, and 0.30:0.47 cm 3  cm −3 for the 105–120 cm soil layer. The available soil water up to 120 cm depth observed in this study was 216 mm in 2009–10 and 207 mm in 2010–11 (Purushothaman et al, 2016a). The bulk density was 1.35 g cm −3 for the 0–15 cm soil layer and 1.42 g cm −3 for the 105–120 cm soil layer (El-Swaify et al, 1985).…”
Section: Methodsmentioning
confidence: 53%
“…The emphasis placed upon RDp as an important trait for deeper soil water extraction to enhance reproductive growth and grain yield under DS (Saxena et al, 1993, Krishnamurthy et al, 2003, Zhang et al, 2004, Kashiwagi et al, 2005, Kirkegaard et al, 2007, Purushothaman et al, 2016a) had been confirmed to be appropriate with this work. The genotype ICC 4958 had a strong root system as early as 35 DAS, flowered and matured about 10 days earlier than mean flowering time.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations